2022
DOI: 10.5194/os-18-1055-2022
|View full text |Cite
|
Sign up to set email alerts
|

Deep through-flow in the Bight Fracture Zone

Abstract: Abstract. Iceland–Scotland Overflow Water (ISOW) is exported from the Nordic Seas into the Iceland Basin to feed the lower limb of the Meridional Overturning Circulation. The Bight Fracture Zone (BFZ) is known to be a major route for ISOW toward the Irminger Sea, but the role of this gateway in the evolution of ISOW properties over the subpolar gyre is unclear. A combination of ship-based and Deep-Argo data gathered between 2015 and 2018 allows us to investigate the pathways and hydrographic evolution of ISOW … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
(57 reference statements)
0
7
1
Order By: Relevance
“…Small clusters of Deep Argo floats have demonstrated their ability to detect the reversal of a long-term freshening trend in the Australian Antarctic Basin, at higher temporal and spatial resolution than historical shipboard CTD occupations (Thomas et al, 2020;Foppert et al, 2021). By providing simultaneous temperature and salinity profiles over broad swaths of ocean basins, Deep Argo has proven effective at mapping large-scale circulation pathways of dense water masses formed near Antarctica (Thomas et al, 2020;Foppert et al, 2021), in the subpolar North Atlantic Ocean (Racapéet al, 2019;Petit et al, 2022), and in the Southwest Pacific Ocean (Zilberman et al, 2020; Figures 4A, B) with unprecedented detail. Seasonal fluctuations in the recirculation of the Deep Western Boundary Current of the Southwest Pacific Basin, and associated forcing mechanisms, were detected for the first time (Zilberman et al, 2020;Figures 4C), as was a slowdown of flow of AABW into the Argentine Basin (Johnson, 2022).…”
Section: Value Of Deep Argo Datamentioning
confidence: 99%
“…Small clusters of Deep Argo floats have demonstrated their ability to detect the reversal of a long-term freshening trend in the Australian Antarctic Basin, at higher temporal and spatial resolution than historical shipboard CTD occupations (Thomas et al, 2020;Foppert et al, 2021). By providing simultaneous temperature and salinity profiles over broad swaths of ocean basins, Deep Argo has proven effective at mapping large-scale circulation pathways of dense water masses formed near Antarctica (Thomas et al, 2020;Foppert et al, 2021), in the subpolar North Atlantic Ocean (Racapéet al, 2019;Petit et al, 2022), and in the Southwest Pacific Ocean (Zilberman et al, 2020; Figures 4A, B) with unprecedented detail. Seasonal fluctuations in the recirculation of the Deep Western Boundary Current of the Southwest Pacific Basin, and associated forcing mechanisms, were detected for the first time (Zilberman et al, 2020;Figures 4C), as was a slowdown of flow of AABW into the Argentine Basin (Johnson, 2022).…”
Section: Value Of Deep Argo Datamentioning
confidence: 99%
“…ISOW continues southwestward as a deep boundary current along the eastern flank of the RR and is partially siphoned off into the Irminger Sea to the west through gaps in the ridge (e.g., Petit et al., 2022). The first major gap in the RR with sill depth deeper than 2,000 m is the Bight Fracture Zone (BFZ) at ∼56.7°N (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…At the BFZ (57°N), Xu et al found the mean transport to be 0.4 Sv, and mean velocities to be ∼2-5 cm/s westward. Synoptic observational transport estimates across the BFZ range from 1.3 ± 0.1 and 0.3 ± 0.1 Sv (from Lowered Acoustic Doppler Current Profiler (LADCP) sections; Petit et al, 2022) and 0.8 ± 0.8 Sv (from geostrophic estimates; Petit et al, 2018). Using Deep-Argo profiling floats set to drift at 1,900-2,100 dbar, Petit et al (2022) showed the westward pathway of ISOW through the BFZ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations